Timing stability of three black widow pulsars. Issue 2 (7th April 2020) - Bak Nielsen, Ann-Sofie; Janssen, Gemma H; Shaifullah, Golam; Verbiest, Joris P W; Champion, David J; Desvignes, Grégory; Guillemot, Lucas; Karuppusamy, Ramesh; Kramer, Michael; Lyne, Andrew G; Possenti, Andrea; Stappers, Ben W; et al.
ABSTRACT: We study the timing stability of three black widow pulsars (BWPs), both in terms of their long-term spin evolution and their shorter term orbital stability. The erratic timing behaviour and radio eclipses of the first two BWP systems discovered (PSRs B1957+20 and J2051−0827) were assumed to be representative for this class of pulsars. With several new black widow systems added to this population in the last decade, there are now several systems known that do not show these typical orbital variations or radio eclipses. We present timing solutions using 7–8 yr of observations from four of the European Pulsar Timing Array telescopes for PSRs J0023+0923, J2214+3000, and J2234+0944, and confirm that two of these systems do not show any significant orbital variability over our observing time span, both in terms of secular or orbital parameters. The third pulsar PSR J0023+0923 shows orbital variability and we discuss the implications for the timing solution. Our results from the long-term timing of these pulsars provide several new or improved parameters compared to earlier works. We discuss our results regarding the stability of these pulsars, and the stability of the class of BWPs in general, in the context of the binary parameters, and discuss the potential of the Roche lobe filling factor of the companion star being an indicator for stability of these systems.